Costa Rica : Investment Climate Assessment - World Bank (Washington, DC, 2012)
The objective of the Costa Rica Investment Climate Assessment (ICA) is to evaluate constraints on growth of the private sector in Costa Rica using a survey of 343 manufacturing firms known as the Investment Climate Survey (ICs) and a Logistic Survey in 75 firms in three export sectors (processed foods, cut flowers and plants, and medical equipment). This assessment focuses on the microeconomic and structural dimensions of the nation's business environment, viewed from an international perspective. In evaluating the most important investment climate constraints affecting Costa Rican establishments, this report uses both subjective and objective indicators. The emphasis is placed on the second type of information. Surveyed Costa Rican firms perceive macroeconomic instability, anti-competitive and informal practices, and cost and access to financing as the four major obstacles to growth in Costa Rica. Transport and corruption issues are also among the top major or severe constraint for Costa Rican firms. When asked to select the main obstacle to growth, surveyed manufacturing firms cited financial constraints as their predominant problem, followed by anti-competitive/informal practices, macroeconomic stability and red tape/regulation. A number of investment climate indicators drawn from the ICs were econometrically related to measures in productivity. Overall results of the ICs show that variables in all four categories of investment climate affect Costa Rican firms in terms of their productivity. In addition to the analysis on firm productivity, the econometric analysis looked at the effect of investment climate variables on the probability of exporting. The conclusions of the econometric analysis are that investment climate variables significantly affect total factor productivity and that increased emphasis on governance and business regulation, infrastructure, and innovation is appropriate. The results shown are consistent with firms' perceptions that put infrastructure and regulatory issues as severe obstacles to growth.